Fibrinous iritis due to oxybuprocaine. Issue 1 (January 1989) - Haddad, R
Abstract : Following minor surgery performed under topical application of oxybuprocaine (Dorsacaine, Novesin) two patients suffered from fibrinous iritis and moderate corneal swelling. We believe that this represents a toxic reaction caused by an inadvertent entry of this drug into the anterior chamber during the procedure.